Physical Characteristics of American Football Players, According to their Playing Position, Belonging to a Club in the Biobío Region - Campos - Campos, Kevin (2025)
Introduction: American football is a sport of high physical demand, where the performance of players largely depends on strength, power, and agility —attributes that vary according to the position occupied on the field—. While numerous studies have characterized these positional differences, the evidence remains limited in regions where the sport is still developing, such as Chile. Objective: To compare the physical qualities of American football players of a club in the Biobío region, according to their playing positions. Methodology: 22 male American soccer athletes (21.6±4.6 years) participated and were divided into three groups, i.e., linemen (LM), skill players (SP) and high skill players (BSP). For the evaluation of physical qualities, the NFL Combine tests were used. Results: The results show that there were significant differences between BSP and LM players in the lower extremity power test (215±21 cm versus 187±12 cm, respectively, p=0.019). On the other hand, it is highlighted that in the agility tests the SP athletes presented better results than the LM (3 cone drill: 8.6±0.3 s versus 9.4±0.4 s, respectively, p=0.045 and Pro-agility drill: 4.4±0.1 s versus 4.9±0.3 s, respectively, p=0.012). Likewise, it was observed that, in the power test, SP got better results compared to LM. On the other hand, in the maximum strength test for lower extremities, the BSP reached better results than the other positions, although the effect of this difference is small. Conclusion: It is concluded that the athletes of the Biobío region club present specific characteristics according to their position on the playing field. However, LM players showed a significantly lower performance than expected in terms of maximal strength, attending to their roles on the playing field.